Contenidos de aprendizaje para estudiantes de diseño en podcast - Contreras Espinosa, Ruth S.; Eguia Gómez, José Luis (Cuadernos de Documentación Multimedia, 2009)
The Universitat Politècnica de Catalunya, through its degree in Design, has done an pioneering experience combining the learning contents and the new technologies, such as the podcasting services, looking for bringing to the students mobile devices the learning contents.
Keywords: Podcast; m-learning; Blended learning; Design; Learning contents